BABY-LED WEANING, AN OVERVIEW OF THE NEW APPROACH TO FOOD INTRODUCTION: INTEGRATIVE LITERATURE REVIEW - Melisa Sofia Gomez; Ana Paula Toneto Novaes; Janaina Paulino da Silva; Luciane Miranda Guerra; Rosana de Fátima Possobon (Sociedade de Pediatria de São Paulo, 2020)
ABSTRACT Objective: To analyze the scientific literature on Baby-Led Weaning with an integrative literature review to identify risks and benefits. Data source: The databases used were: National Library of Medicine (MEDLINE), Latin American and Caribbean Literature in Health Sciences (LILACS - Literatura Latino-Americana e do Caribe em Ciências da Saúde), US National Library of Medicine (PubMed), and Virtual Health Library (BVS - Biblioteca Virtual em Saúde) in December 2017. The inclusion criteria established were publications in English with the descriptor "baby-led weaning" in the heading, abstract, or keywords, classified as original articles, of primary nature, and available online and in full. We excluded review articles, editorials, letters to the editor, critical commentaries, and books on the subject, as well as articles not available in full and duplicates. Data summary: We identified 106 articles, of which 17 met the selection criteria. The Baby-Led Weaning method was significantly associated with the baby's satiety, the start of complementary feeding, and adequacy of weight gain. On the other hand, choking and the intake of micronutrients were negatively associated, however with no statistical differences. Conclusions: Despite the benefits found, the risks still deserve attention and should be investigated with longitudinal randomized controlled studies to ensure the safety of the method when practiced exclusively.